Criminalidade violenta e fragmentação urbana na Grande Vitória - Zanotelli, Cláudio; Raizer, Eugenia Célia; Lira, Pablo Silva; Oliveira, Eldon Gramlich; Barros, Ana Maria Leite de (Geografares, 2006)
DOI: 10.7147/GEO5.1054